Stress changes, focal mechanisms, and earthquake scaling laws for the 2000 dike at Miyakejima (Japan). Issue 6 (24th June 2015) - Passarelli, Luigi; Rivalta, Eleonora; Cesca, Simone; Aoki, Yosuke
Abstract: Faulting processes in volcanic areas result from a complex interaction of pressurized fluid‐filled cracks and conduits with the host rock and local and regional tectonic setting. Often, volcanic seismicity is difficult to decipher in terms of the physical processes involved, and there is a need for models relating the mechanics of volcanic sources to observations. Here we use focal mechanism data of the energetic swarm induced by the 2000 dike intrusion at Miyakejima (Izu Archipelago, Japan), to study the relation between the 3‐D dike‐induced stresses and the characteristics of the seismicity. We perform a clustering analysis on the focal mechanism (FM) solutions and relate them to the dike stress field and to the scaling relationships of the earthquakes. We find that the strike and rake angles of the FMs are strongly correlated and cluster on bands in a strike‐rake plot. We suggest that this is consistent with optimally oriented faults according to the expected pattern of Coulomb stress changes. We calculate the frequency‐size distribution of the clustered sets finding that focal mechanisms with a large strike‐slip component are consistent with the Gutenberg‐Richter relation with a b value of about 1. Conversely, events with large normal faulting components deviate from the Gutenberg‐Richter distribution with a marked roll‐off on its right‐hand tail, suggesting a lack of large‐magnitude events ( M w > 5.5). This may result from the interplay of the limited thickness and lower rock strength of the layer of rock above the dike, where normal faulting is expected, and lower stress levels linked to the faulting style and low confining pressure. Key Points: FMs compatible with the calculated Coulomb stress changes induced by the dike Faulting styles induced by dike range from strike slip to oblique and normal faulting Normal faulting does not follow a Gutenberg‐Richter statistics